Shifting away from the business-as-usual approach to research conferences - Chelsie W. W. Counsell; Franziska Elmer; Judith C. Lang (Biology Open, 2020)
To combat the climate crisis, we need rapid, unprecedented social change. Scientists can play a lead role by signaling to society that we recognize the critical importance of redesigning our business-as-usual approach to research conferences. Traditional research conferences have high CO2 emissions as well as significant financial and travel time costs for participants. Using available technology, early career scientists Chelsie Counsell and Franziska Elmer created a global, virtual, coral reef research conference with live talks, recorded contributions, and networking events. Funding from The Company of Biologists allowed this event to be free, supporting attendance of 2700 subscribers and content contributions from 165 participants from diverse backgrounds and career stages. We provide metrics on content viewership and participation in networking activities, note the success of incorporating regionally focused sub-events, and discuss the emergence of a collaborative research project. We highlight the broad accessibility of virtual conferences as well as their increased flexibility in programming, health benefits, and cost savings. Our approach to organizing and hosting a global, low-carbon emission research conference is documented. Finally, we propose a hybrid approach to future conferences with virtually connected remote (sub-regional or local) hubs.